Plasticity in the Drosophila larval visual system - Farca-Luna, Abud J.; Sprecher, Simon G. (Frontiers in Cellular Neuroscience, 2013)
The remarkable ability of the nervous system to modify its structure and function is mostly experience and activity modulated. The molecular basis of neuronal plasticity has been studied in higher behavioral processes, such as learning and memory formation. However, neuronal plasticity is not restricted to higher brain functions, but may provide a basic feature of adaptation of all neural circuits. The fruit fly Drosophila melanogaster provides a powerful genetic model to gain insight into the molecular basis of nervous system development and function. The nervous system of the larvae is again a magnitude simpler than its adult counter part, allowing the genetic assessment of a number of individual genetically identifiable neurons. We review here recent progress on the genetic basis of neuronal plasticity in developing and functioning neural circuits focusing on the simple visual system of the Drosophila larva.